Comparative Study of Serological Tests for Mycoplasma synoviae Diagnosis in Commercial Poultry Breeders - R. L. Luciano; A. L. S. P. Cardoso; G. F. Z. Stoppa; A. M. I. Kanashiro; A. G. M. de Castro; E. N. C. Tessari (Veterinary Medicine International)
Avian mycoplasmosis causes great economic losses to the poultry industry, and one of the major agents involved is Mycoplasma synovie (MS). Serum from commercial poultry breeders (𝑛=2781) was tested for MS by serum plate agglutination (SPA), hemagglutination inhibition (HI), and enzyme-linked immunosorbent assay (ELISA). From 2,781 samples tested, 736 (26.46%) were positive in SPA. From 712 SPA-positive sera, 30 samples (4.21%) were positive in HI, and 150 samples (21.06%) were positive in ELISA. Copositivity between ELISA and HI was 90%, and conegativity was 82.0%. Agreement between HI and ELISA was rejected by McNemar's test (𝑃≤.001), and Kappa coefficient showed a weak correlation between the two techniques (𝑘=0.25; 0.21≤𝑘<0.40). Weak statistical correlation was observed between all serological tests (SPA, HI, and ELISA), and they should only be used for initial screening for MS.